Enhancing biohydrogen gas production in anaerobic system via comparative chemical pre-treatment on palm oil mill effluent (POME). (1st November 2022) - Arisht, Shalini Narayanan; Mahmod, Safa Senan; Abdul, Peer Mohamed; Indera Lutfi, Abdullah Amru; Takriff, Mohd Sobri; Lay, Chyi-How; Silvamany, Hemavathi; Sittijunda, Sureewan; Jahim, Jamaliah Md
Abstract: Biological hydrogen production using palm oil mill effluent (POME) as a carbon source through dark fermentation process has been suggested to be a promising bioenergy potential and enacts as alternative renewable energy source. Results have indicated that among various 1.5% (w/v) chemical pre-treatments (sodium hydroxide, NaOH; hydrochloric acid, HCl; sulphuric acid, H2 SO4 ; phosphoric acid, H3 PO4 and nitric acid, HNO3 ) on POME, using H3 PO4 would generate maximum biohydrogen production of 0.193 mmol/L/h, which corresponded to a yield of 1.51 mol H2 /mol TCconsumed with an initial total soluble carbohydrate concentration of 23.52 g/L. Among H3 PO4 concentrations (1%–10%), the soluble carbohydrate content and the biohydrogen produced was highest and increased by 1.70-fold and 2.35-fold respectively at 2.5% (w/v), as compared to untreated POME. The batch fermentation maximum hydrogen production rate and yield of 0.208 mmol/L/h and 1.69 mol H2 /mol TCconsumed were achieved at optimum pre-treatment conditions of pH 5.5 and thermophilic temperature (60 °C). This study suggests that chemical pre-treatment approaches manage to produce and improve the carbohydrate utilisation process further. Continuous fermentation in CSTR at the optimum conditions produce heightened 1.5-fold biohydrogen yield for 2.5% H3 PO4 at 6 h HRT as compared to batch scale. Bacterial community via next-generation sequencing analysis at optimum HRT (6 h) revealed that Thermoanaerobacterium thermosaccharolyticum registered the highest relative frequency of 20.24%. At the class level, Clostridia, Bacilli, Bacteroidia, Thermoanaerobacteria, and Gammaproteobacteria were identified as the biohydrogen-producing bacteria in the continuous system. Insightful findings from this study suggest the substantial practical utility of dilute chemical pre-treatment in improving biohydrogen production. Graphical abstract: Image 1 Highlights: Acid pre-treatment of POME enhanced biohydrogen production than alkaline treatment. 2.5% (w/v) H3 PO4 pre-treatment at 20 min increased total sugar content by 2-fold. pH 5.5 and temperature of 60 °C represented optimum pre-treatment conditions. CSTR at 6-h HRT produced HY of 2.25 molH₂ /molTC from pre-treated POME. Biohydrogen attributed to genera Thermoanaerobacterium, Clostridium and Bacillus.